Particleboard properties from 2.0mm wood waste particle size in relation to different board density and resin content / Ahmad Hafizuddin Asha'ari - Asha'ari, Ahmad Hafizuddin (Faculty of Applied Sciences, 2016)
Arise of logging activities cause lowing preserve of soil and the habitat for flora and fauna been reduced due increased demand for wooden materials every year. Besides, one of the alternatives for solid wood furniture which quite popular materials have been used nowadays for exterior and interior was particleboard. In these studies, the main aim to determine mechanical and physical properties from wood waste had been used a raw material for particleboard manufacturing related to different density of board and resin content usage. Two different board densities were use; 650 kg/m3 represented low density board and 750 kg/m3 represented higher density board. 8%, 10% and 12% of resin content were used as another parameter with usage of Urea Formaldehyde as an adhesive. The result showed that particleboard with 750 kg/m3 board density within 12% resin content have the higher value for bending strength and Internal bonding while thickness swelling and water absorption was the lowest values.